Operational issues in preventing mother-to-child transmission of HIV-1 in Abidjan, Côte d'Ivoire, 1998-99 - Msellati Philippe; Hingst Gepke; Kaba Fanta; Viho Ida; Welffens-Ekra Christiane; Dabis François (The World Health Organization, 2001)
OBJECTIVE: To demonstrate the feasibility, from the public health standpoint, of preventing mother-to-child transmission of human immunodeficiency virus type 1 (HIV-1) in Africa. METHODS: Voluntary counselling and HIV serotesting were routinely provided in four health centres in Abidjan, Côte d'Ivoire, for six months in 1998-99. Peripartum treatment with zidovudine and alternatives to breastfeeding were provided free to HIV-infected women. FINDINGS: Of the 4309 pregnant women in the study who attended their first antenatal care visit, 3756 benefited from individual counselling and pretesting (87.2%), and 3452 (80.1%) agreed to undergo HIV serotesting. Overall HIV prevalence was (12.89%) and 5% for women aged under 18 years. Among the 2998 HIV-negative women, 71% returned for their test result, whereas only 60% of the 445 HIV-positive women did so. A total of 124 HIV-positive women were informed of their serostatus and the possibility of preventing mother-to-child transmission of HIV; 100 started treatment and 80 completed zidovudine prophylaxis. At 6 weeks of age, 36 of the 78 liveborn children were being breastfed (46%), two were being mixed-fed and 41 (52%) were being artificially fed. CONCLUSION: In Abidjan, voluntary counselling and HIV testing with a view to preventing mother-to-child transmission was feasible in antenatal care units and was well accepted by pregnant women. An insufficient proportion of women returned to obtain their test results. This was especially so among HIV-positive women, the target group for preventing mother-to-child transmission of HIV. Additional staff were required in order to offer voluntary counselling and HIV testing to the study women. Close supervision and strong commitment of health workers were essential. Alternatives to breastfeeding were effectively proposed to HIV-positive women, with active follow-up of children and clinical, nutritional and social support.